2022
DOI: 10.1111/jcmm.17449
|View full text |Cite
|
Sign up to set email alerts
|

Syringic acid mitigates isoproterenol‐induced cardiac hypertrophy and fibrosis by downregulating Ereg

Abstract: Cardiomyocytes, which exhibit postmitotic characteristics, do not divide but exhibit growth in response to various stresses. The hallmarks of cardiomyocyte hypertrophy involve the activation of foetal gene program, upregulation of protein synthesis and reorganization of sarcomeres. 1 Cardiac hypertrophy is a hallmark feature of various cardiovascular diseases, including myocardial infarction, hypertension, heart failure and valvular diseases. 2 Although short-term cardiac hypertrophy can be beneficial, long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…At the conclusion of this study, it was indicated that syringic acid can reduce the effects of diabetic cardiomyopathy by improving the levels of creatine kinase-myocardial band (CK-MB) and lactate dehydrogenase (LDH), reducing lipid peroxidation and protein carbonylation in the heart. In another similar study, Han et al examined the effects of syringic acid on cardiac hypertrophy and fibrosis in isoproterenol-treated mice and cells [ 29 ]. In the results of their study, it was stated that syringic acid was found to mitigate isoproterenol-induced upregulation of Ereg, Myc, and Ngfr.…”
Section: Discussionmentioning
confidence: 99%
“…At the conclusion of this study, it was indicated that syringic acid can reduce the effects of diabetic cardiomyopathy by improving the levels of creatine kinase-myocardial band (CK-MB) and lactate dehydrogenase (LDH), reducing lipid peroxidation and protein carbonylation in the heart. In another similar study, Han et al examined the effects of syringic acid on cardiac hypertrophy and fibrosis in isoproterenol-treated mice and cells [ 29 ]. In the results of their study, it was stated that syringic acid was found to mitigate isoproterenol-induced upregulation of Ereg, Myc, and Ngfr.…”
Section: Discussionmentioning
confidence: 99%